(untitled) (International journal of medical sciences, 2026)
Thyroid nodules are one of the most common findings in modern clinical endocrinology and radiology. The expansion of the use of ultrasound diagnostics and screening programs has led to a significant increase in their detection rate. According to epidemiological data, thyroid nodules can be detected by ultrasound examination in 60–70% of the adult population [1,2]. Although the majority of detected nodules are benign, a malignant process is detected in approximately 5–15% of cases, which requires accurate risk stratification and informed patient selection for invasive diagnostic procedures [3,4].